CIRCULAR POLARIZATION IN A $2D$ PERIODIC ARTIFICIAL ANISOTROPIC DIELECTRIC MEDIUM - Sargsyan, Armen N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The phenomenon of polarization rotation in dielectric periodic structures is quite interesting. A similar structure was used in a sample with a 2D artificial periodic structure, where the plane wave propagation method was applied. Anisotropic dielectric constants were obtained, which were used for polarization rotation, and polarization rotation in an anisotropic medium was studied based on the dielectric permittivity of the effective medium. Those relationships, quantities, and parameters depending on the dielectric medium, dielectric permittivity, and 2D periodic structure have been studied and analyzed, which provide control of the degree of anisotropy, i.e. provide a distinction between fast and slow modes, which in turn provide the best polarization rotation per unit length.
Keywords: anisotropic medium; dielectric periodic structure; dielectric permittivity; circular polarization; navigation; radar